The Influence of Subjective Well-Being and Learning Motivation on Mathematics Learning Outcomes in 10th Grade at SMA Negeri 11 Samarinda - Syahrul Ramadhanul Fajri; Haeruddin Haeruddin; Berahman Berahman; Auliaul Fitrah Samsuddin (Borneo Educational Journal (Borju), 2026)
Indonesian students continue to face difficulties in mathematics, as reflected in their low PISA performance. Besides cognitive mastery, non-cognitive factors such as Subjective Well-Being (SWB) and learning motivation also play an important role in shaping students’ academic outcomes. However, previous findings regarding the influence of SWB on achievement have been inconsistent, suggesting the need to examine it alongside other psychological factors. This study investigates the influence of SWB and learning motivation on the mathematics learning outcomes of 10th-grade students at SMA Negeri 11 Samarinda. A quantitative causal-comparative design was used with three randomly selected classes as the sample. SWB and learning motivation data were collected using a Likert-scale questionnaire, while mathematics outcomes were obtained from students’ report cards. The data were analyzed using truncated spline nonparametric regression. The results indicate that both SWB and learning motivation significantly affect mathematics learning outcomes, individually and simultaneously. These findings highlight the importance of supporting students’ psychological well-being and motivation to enhance mathematics achievement at the senior high school level